A New Mononuclear Manganese(III) Complex of an Unsymmetrical Hexadentate N3O3 Ligand Exhibiting Superoxide Dismutase and Catalase-like Activity: Synthesis, Characterization, Properties and Kinetics Studies - Ledesma, Gabriela Nanci (2015)
A mononuclear MnIII complex MnL·4H2O (H3L = 1-[N-(2-pyridylmethyl),N-(2-hydroxybenzyl)amino]-3-[N′-(2-hydroxybenzyl),N′-(4- methylbenzyl)amino]propan-2-ol) has been prepared and characterized. This complex catalyzes the dismutation of superoxide efficiently, with catalytic rate constant kcat=1.7 × 106M−1 s−1 and IC50 1.26 μM, obtained through the nitro blue tetrazoliumphotoreduction inhibition superoxide dismutase assay, in aqueous solution of pH 7.8. MnL is also able to disproportionate more than 300 equivalents of H2O2 in CH3CN, with initial rate of H2O2 decomposition given by ri=kcat [MnL]2 [H2O2]and kcat = 1.32 (2) mM−2 min−1. The accessibility of the MnIV state (Ep = 0.53 V vs. saturated calomel electrode), suggests MnL employs a high-valent catalytic cycle to decompose O2?− and H2O2.